Introduction to cryptography - Padhye, Sahadeo; Sahu, Rajeev Anand; Saraswat, Vishal (CRC Press, Taylor & Francis Group, 2018)
Electronic communication and financial transactions have assumed massive proportions today. But they come with high risks. Achieving cyber security has become a top priority, and has become one of the most crucial areas of study and research in IT. This book introduces readers to perhaps the most effective tool in achieving a secure environment, i.e. cryptography. This book offers more solved examples than most books on the subject, it includes state of the art topics and discusses the scope of future research.